Imagination : a Study in the History of Ideas. - Cocking, J. M. (Routledge, 1991)
Explores the history of imagination from antiquity to the Renaissance. The author looks at the writings of Aristotle and Plato, developments in the Middle Ages, with particular attention paid to parallel traditions in Islamic thought, Dante, and the Neo-platonists.